Generation of a novel fully human non-superagonistic anti-CD28 antibody with efficient and safe T-cell co-stimulation properties - Abdullah Elsayed; Christian Pellegrino; Louis Plüss; Frederik Peissert; Ramon Benz; Franziska Ulrich; Gudrun Thorhallsdottir; Sheila Dakhel Plaza; Alessandra Villa; Jacqueline Mock; Emanuele Puca; Roberto De Luca; et al. (Taylor & Francis Group, 2023)
ABSTRACTAntibody-based therapeutics represent an important class of biopharmaceuticals in cancer immunotherapy. CD3 bispecific T-cell engagers activate cytotoxic T-cells and have shown remarkable clinical outcomes against several hematological malignancies. The absence of a costimulatory signal through CD28 typically leads to insufficient T-cell activation and early exhaustion. The combination of CD3 and CD28 targeting products offers an attractive strategy to boost T-cell activity. However, the development of CD28-targeting therapies ceased after TeGenero's Phase 1 trial in 2006 evaluating a superagonistic anti-CD28 antibody (TGN1412) resulted in severe life-threatening side effects. Here, we describe the generation of a novel fully human anti-CD28 antibody termed "E1P2" using phage display technology. E1P2 bound to human and mouse CD28 as shown by flow cytometry on primary human and mouse T-cells. Epitope mapping revealed a conformational binding epitope for E1P2 close to the apex of CD28, similar to its natural ligand and unlike the lateral epitope of TGN1412. E1P2, in contrast to TGN1412, showed no signs of in vitro superagonistic properties on human peripheral blood mononuclear cells (PBMCs) using different healthy donors. Importantly, an in vivo safety study in humanized NSG mice using E1P2, in direct comparison and contrast to TGN1412, did not cause cytokine release syndrome. In an in vitro activity assay using human PBMCs, the combination of E1P2 with CD3 bispecific antibodies enhanced tumor cell killing and T-cell proliferation. Collectively, these data demonstrate the therapeutic potential of E1P2 to improve the activity of T-cell receptor/CD3 activating constructs in targeted immunotherapeutic approaches against cancer or infectious diseases.